Aradidae from Vietnam III. Trichosomaptera gibbosa n.gen., n.sp., an apterous Carventinae (Hemiptera: Heteroptera: Aradidae) - Pham, Minhlan; Bai, Xiaoshuan; Heiss, Ernst; Cai, Wanzhi (Zootaxa, 2014)
A new apterous flat bug genus of the subfamily Carventinae, Trichosomaptera n.gen., is described and illustrated to accommodate gibbosa n. sp. from Vietnam. The species could not be placed in any known genus.